Inventarisasi Predator Pada Intercroping Kopi Dan Cabai Rawit Di Kabupaten Aceh Tengah - pratiwi, vinny; Harta, Rika Yusli; Ritaqwin, Zaitun; Yarni, Fuja (Jurnal Sains Pertanian, 2024)
Coffee plants are annual plants and chili plants are seasonal plants that can usually grow together. The morphology of coffee and chili plants consists of several main components, namely consisting of roots, stems, leaves, flowers, fruits and seeds so as to optimize the implementation of this research conducted in Pedemun Village, Lut Tawar District, Central Aceh Regency from March to April 2023. This research was conducted using descriptive survey method. Sampling was determined by purposive sampling using 4 types of traps, namely yellow plate traps, net traps, sweet juice and pheromones. Insect observations and sampling were carried out at one time period, namely 07.00-09.00 every one week, in sunny or non-rainy weather conditions. Observations were made by identifying trapped predators, and collecting them according to the type of predator, and preserving each predator sample.Based on the observations made, there were 152 predator individuals belonging to 14 species, of which in the order Diptera family syphidae many trapped pest predators are 53 individuals and in the order Diptera family tachinidae 31 individuals and found junga predators in the order hemittera family lygaeldea 22 individuals in the order coleoptera family coccineliit 18 individuals, which occupy the most trapped predators. The results of the study are known from the number of 14 predator species found in coffee and chili plants, the data of the diversity index of predatory insect species is 1.92 which shows the category of moderate diversity. Of the 14 species of predators of coffee and chili plants, the most predators caught were syiphid flies as many as 53 individuals, on average attacking pest plants on coffee and chili plants